Mechanical loading response in trabecular bone is abrogated by sclerostin - A direct demonstration - Khalid, Kamarul Ariffin; Kogawa, Masakazu; Wijenayaka, Asiri R; Findlay, David M; Atkins, Gerald J (Australian Health and Medical Research Council, 2012)
Sclerostin is expressed almost exclusively by mature osteocytes in bone. Recent findings from this lab indicate that sclerostin targets pre-osteocytes and osteocytes to regulate bone mineralisation(1), osteoclast activity(2), and, potentially, osteocytic osteolysis(3). Sclerostin expression in vivo is associated with the response of osteocytes to mechanical loading and unloading.